Spécificités des mollusques, conditions de mise en oeuvre chez l'huître creuse Crassostrea gigas à l'échelle de l'écloserie et premiers résultats de terrain - Gerard, Andre (International Conference "Bordeaux Aquaculture '94," Bordeaux, France, March 23-25, 1994. Eur. Aquacult. Soc. Spec. Publ., 1994)
The reproduction effort in Crassostrea gigas, as in most bivalve molluscs, has priority over their somatic growth. At the beginning of spring, the energetic metabolic processes are geared towards gametogenesis over glucidic stocks, thus inducing a slowing down of the growth and a change in the organoleptic qualities of the flesh (Héral & Deslous-Paoli, 1983). The same authors showed that this effort increases along with age (figure 1). In young one-year-old oysters, the energy is mostly burnt in growth, only 18 % is involved in reproduction, whereas in two-year-old oysters, 60 to 65 % of the energy is used for gamete formation (Deslous-Paoli & Héral, 1983). In order to limit the impact of gonadogenesis and to try and re-orientate this energy flux towards somatic growth and stock constitution, one of the research methods that have been developed for about ten years aims to obtain sterile individuals through triploidisation. In molluscs, research has been triggered in the US on the following species: Crassostrea virginica (Stanley et al., 1981), Crassostrea gigas (Downing & Allen, 1987; Allen & Downing, 1986 1990), Argopecten irradians (Tabarini, 1984), Haliotis discus (Arai et al., 1986). These experiments demonstrated, especially in Crassostrea gigas, a partial sterility of triploid individuals, going hand in hand with an improvement in growth performances and a constant high glycogen content all year long (Allen & Downing, 1986 1990). [.] L'effort de reproduction chez Crassostrea gigas, comme pour la plupart des mollusques bivalves est prioritaire sur la croissance somatique. Dès le début du printemps, le métabolisme énergétique est principalement orienté vers la gamètogenèse au détriment des réserves glucidiques. induisant ainsi un ralentissement de la croissance et une modification des qualités organoleptiques de la chair (Héral & Deslous-Paoli, 1983). Ces mêmes auteurs ont montré que cet effort augmente avec l'âge (figure 1). Chez les jeunes huîtres de 1 an, l'énergie est ...